Types of Links between Verbal and Visual Components in “Urban Message” of Irkutsk - S. N. Lokhov (Научный диалог)
The question of peculiarities of the language environment of the city is considered. The definition of the term urban message , which the author of the article refers to banners, billboard advertising and signs. Trends in the study of creolized texts in modern linguistics are described. The main reasons for the frequent use of paralinguistic elements in the advertising text in general and in the “urban message” in particular are noted. The links (connectivity) between verbal component and the visual part in the texts of the urban environment of Irkutsk are examined. The relevance of the research is determined by the need to assess the effectiveness of the impact of texts on the audience. The novelty of the work is seen in the fact that for the first time “urban message” as a kind of advertising text acts as a full-fledged object of linguistic research. The results of the Irkutsk “urban message” analysis are presented. Classification of types of semantic relations of verbal and visual components is given: (1) direct correlation, (2) peripheral relevance, (3) contamination (complementarity) of verbal-visual unit and ergonym. It is established that the authors of creolized texts prefer the first type of relation between image and slogan. It is suggested that a small number of examples with other types of links is due to the insufficient level of speech culture of the authors of the “urban message.” Isolated cases of unwarranted (and wrong) use of the element of non-verbal part are identified.